Comparative decomposition rates of piglets buried in manure: a pilot study and implications for forensic taphonomy. Issue 4 (2nd October 2019) - Miles, Kelly
Abstract: Comparative decomposition rates of piglet carcasses were obtained when interred in air, soil, horse manure or pig manure to test the belief that pig manure expedites soft tissue decomposition in forensic cases. Data do not support this claim. Results show initial rapid rates of decomposition variables in air, but piglets buried in soil, horse manure and pig manure caught up to the exposed piglets' decomposition rates by the end of the twelve-day experiment. Both piglet tissues and manure have low C/N ratios (<20:1) as opposed to the optimal composting C/N ratio of 30:1 to yield accelerated decomposition. Limitations of this study are addressed with suggestions for future studies with forensic relevance.